Beetle-inspired wettable materials: from fabrications to applications. (June 2019) - Zhu, H.; Huang, Y.; Lou, X.; Xia, F.
Abstract: Namib Desert beetles ( Stenocara sp.) are featured with superior fog-harvesting abilities attributing to the hydrophilic-hydrophobic patterned surfaces, where water is captured by the hydrophilic patterns and then transported by the hydrophobic areas to feed themselves with the collected water resource. In this review, inspired by the special structures on Namib Desert beetles, the recent developments, including the fabrications and applications, of bioinspired (super)hydrophilic-(super)hydrophobic patterned materials were described. We first introduced the wettable models and then discussed water collection mechanism on the beetle-inspired wetting samples. Then, the fabrication approaches to beetle-inspired materials were showed, which were 'mixing method, ' 'responsive method, ' 'inkjet printing method, ' and 'mask-based method.' Then, the emerging applications based on the (super)hydrophilic-(super)hydrophobic patterned materials were detailed. Except for the well-known fog harvesting, antiicing and oil/water separation, arising from the biphilic topography, on the patterned wettable surfaces were also reported. Moreover, solution coalescence on the (super)hydrophilic patterns surrounded by (super)hydrophobic substrate manifested enriched concentration and enhanced fluorescence effect, indicating excellent performance in the field of biosensing. At last, the challenges and outlooks related to the developments of beetle-inspired wettable materials were presented. Graphical abstract: Inspired by the wetting features on Namib Desert beetles, the recent fabrications and applications based on the bioinspired wettable materials were presented.Image 1